2005
DOI: 10.1111/j.1600-0854.2005.00309.x
|View full text |Cite
|
Sign up to set email alerts
|

CeVPS‐27 is an Endosomal Protein Required for the Molting and the Endocytic Trafficking of the Low‐Density Lipoprotein Receptor‐Related Protein 1 in Caenorhabditis elegans

Abstract: Class E vacuolar protein-sorting (Vps) proteins were first described in yeast as being involved in receptormediated endocytosis and multivesicular body formation. Inactivation by RNA interference of the class E VPS genes of the nematode Caenorhabditis elegans revealed heterogeneous phenotypes. We have further characterized the role of the essential gene Cevps-27, ortholog of human hepatocyte growth factor-regulated tyrosine kinase substrate, during the development of C. elegans. Use of green fluorescent protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
82
1
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(93 citation statements)
references
References 59 publications
9
82
1
1
Order By: Relevance
“…20 A recent study has found that an ortholog of HRS, CeVPS-27 is required in the endosomal and autophagic pathways and play a crucial role in endocytic trafficking of low-density lipoprotein receptor-related protein 1 in Caenorhabditis elegans. 21 Furthermore, at the same time of the publication of our current study, 16 HRS was found to play a crucial role in the maturation of autophagosomes in mammalian cells. 22 This study stems from the idea that phosphatidylinositol 3-phosphate (PI3P) plays crucial roles in endocytic and autophagic membrane trafficking and also binds to HRS via a FYVE domain.…”
mentioning
confidence: 51%
“…20 A recent study has found that an ortholog of HRS, CeVPS-27 is required in the endosomal and autophagic pathways and play a crucial role in endocytic trafficking of low-density lipoprotein receptor-related protein 1 in Caenorhabditis elegans. 21 Furthermore, at the same time of the publication of our current study, 16 HRS was found to play a crucial role in the maturation of autophagosomes in mammalian cells. 22 This study stems from the idea that phosphatidylinositol 3-phosphate (PI3P) plays crucial roles in endocytic and autophagic membrane trafficking and also binds to HRS via a FYVE domain.…”
mentioning
confidence: 51%
“…Growing evidence suggests that there may be a crosstalk between autophagy and endocytic pathway. Inactivation of certain C. elegans Vps genes lead to the accumulation of enlarged endosomal structures and an increase in autophagy (Michelet et al, 2009;Roudier et al, 2005). In addition, certain regulators in autophagy and endocytic pathway are reportedly involved in both processes.…”
Section: Introductionmentioning
confidence: 99%
“…So far, the regulatory mechanisms of C. elegans molting are not yet understood, although about a dozen genes have been identified that lead to molting defects when mutated. These genes can be classified into five categories based on their possible functions: (1) proteases that are used to degrade the old cuticle, including a cathepsin Z-like cysteine protease (Cecpz-1) (Hashmi et al, 2004), and two metalloproteases, nas-36 and nas-37 (Davis et al, 2004;Suzuki et al, 2004); (2) transcriptional regulators, including nhr-23 (Kostrouchova et al, 1998(Kostrouchova et al, , 2001, nhr-25 (Asahina et al, 2000;Gissendanner and Sluder, 2000), and let-19 (Wang et al, 2004); (3) enzymes involved in cholesterol metabolism such as let-767 (Kuervers et al, 2003) or cholesterol transporters such as lrp-1 (Yochem et al, 1999); (4) molecules involved in secretion and extracellular transport such as sec-23 (Roberts et al, 2003) and CeVps-27 (Roudier et al, 2005); (5) others, such as the angiotensin converting enzyme-like non-peptidase acn-1 (Brooks et al, 2003).…”
Section: Introductionmentioning
confidence: 99%